Ethics and Ambiguity: A Critical Study of Charles E. Curran's Ecumenical Ethics of Dialogue - Shields, Richard (My University, 2002)
This study focuses on the social ethics of the Roman Catholic moral theologian Charles E. Curran (b. 1934). For more than four decades Curran has been one of the most influential voices in the renewal of Catholic moral theology in North America. Since the Second Vatican Council (1962-1965) the Roman Catholic Church has undergone changes of monumental proportion, impacting on the church's self-consciousness and requiring creative and unprecedented adjustments in its theology. The Council's commitment to "dialogue with the world" made the area of social ethics into a litmus test of the success of the church's reform. Charles Curran has developed an ethical-theological methodology, representing a revised approach to Aristotelian-Thomistic natural law theory, as a model for that dialogue with the world.
This thesis locates Curran's work in the context of the Vatican Council and of the social-ethics tradition of the Roman Catholic Church over the past one hundred years. Curran's critical response to these factors reveals the impulses and directions he develops in his methodology. His four-step method is explained in terms of its ethical and theological purposes and in relation to its intellectual roots in thinkers such as Bernard Lonergan and Karl Rahner. A major part of the thesis is devoted to four case studies, in which Curran applies his method to substantive, social-ethical questions.
This research identifies the strengths and weakness in Curran's method, pointing out the difficulty of melding a revised natural law method with the exigences of contemporary, empirical thought. The study makes recommendations for correcting inconsistencies and inadequacies of Curran's method along lines that are intellectually compatible with the work he has already completed.
Keywords: Education; Education